Approches interlinguistiques de la complementation verbale: Quels savoirs pour l'enseignant? Quels savoirs pour l'eleve? - (:unkn) unknown (Neuchâtel: Institut des sciences du langage et de la communication, 2002)
This issue deals with verb-object complementation, a complex and controversial but important topic, in particular in connection with the teaching and learning of a second language. The articles are a response to a long debate about the harmonization of grammatical terminology used in schools and the simplification of grammar for students. The subject is of special importance for achieving a better integration of methods used in early language learning. The articles include the following: "Don't Complements Only Complement the Verb? And the Verb, is it not Complemented Only by the Complement?" (Michel Maillard); "What if We Reapplied a Regimen to Grammar?" (Alain Berrendonner); "Verbal Complementation: A Short Introduction to Verbal Valency" (Claire Blanche-Benveniste); "Are the Main Dividing Lines in French Grammar to be Explained Through a Description of Portuguese and Spanish Grammar?" (Maria-Elisete Almeida);"The French 'Faire': A Syntactic, Semantic, and Contrastive Approach (French/Bulgarian)" (Iva Novakova); "French Speakers Faced with the German Language: A Hopeless Case?" (Anton Naf); "Quotation and Verbal Complementation in Text Elaboration for Students of French as a Second Language" (Therese Jeanneret); and "Should Past Participle Agreement Rules be Relaxed?" (Marie-Jose Beguelin). (AS)